The dynamics of mosque fund management in Old Order Indonesia - Fahmi, Rizqi Anfanni; Fauzia, Amelia; Razzaq, Abdur (Journal of Islamic Economics Lariba, 2026)
Introduction The management of mosque funds in Indonesia during the Old Order period (1945-1965) played a vital role in religious and social life. Mosques became central to national identity and cohesion, supported by Ad Hoc committees. This study examines the balance between state control and local autonomy in mosque fund management.ObjectivesThis study investigates the dynamics of mosque fund management in the Old Order period, focusing on the roles of Ad Hoc committees and the Ministry of Religious Affairs. It aims to explore how state intervention and Islamic charitable practices like zakat and waqf influenced mosque sustainability and governance.MethodA historical methodology is used, involving four stages: heuristics (source identification), verification (source cross-checking), interpretation (data analysis), and historiography (situating the study in literature). Primary and secondary sources, including government records and newspapers, are analyzed to understand mosque fund management during Indonesia's early independence period.ResultsFindings reveal a balance between local autonomy and centralized state control in mosque fund management. Ad Hoc committees fostered community involvement, while the Ministry of Religious Affairs centralized governance, affecting local autonomy. Islamic charitable practices, particularly zakat and waqf, were crucial for mosque sustainability but faced governance challenges.ImplicationsThis study highlights the need for balancing government regulation with local community participation in mosque management. It also emphasizes the significance of Islamic charitable practices, suggesting that integrating local needs with state oversight can lead to more sustainable and transparent religious institution management.Originality/NoveltyThis research contributes new insights by examining mosque fund management during Indonesia's Old Order period, focusing on the interaction between local governance and state control. It offers a unique historical perspective on the challenges and successes of mosque management, enriching the understanding of post-colonial religious governance.